Land cover and use in the southeast of the province of La Pampa (Argentina) during the period 1980-2020 (Huellas, 2022)
Knowing the dynamics of an ecosystem is essential to understand the relationships between the different components and the problems that are generated within it. On the other hand, a temporal analysis is necessary to evaluate the transformations that occur in that space. The caldén forest has undergone severe transformations over time that impacted on its surface and its appearance. For this reason, the present work aims to analyze the changes in vegetation cover and land uses for the period 1980-2020, in the departments of Guatraché and Hucal, province of La Pampa. For these, a supervised classification of LANDSAT satellite images from 1987 and 2020 was carried out, using the QGis Geographic Information System. Maps of coverage and land use of the study area were obtained and six categories of analysis were defined. The results show a reduction of the caldén forest, both in its open and closed physiognomy and an increase in the areas destined for agricultural activities. However, it was also found that in some areas there is a recovery of the caldenal.
Keywords: changes in cover vegetation; calden forest; agricultural activities; La Pampa